Remembering Components of Food in Drosophila - Das, Gaurav; Lin, Suewei; Waddell, Scott (Frontiers in Integrative Neuroscience, 2016)
Remembering features of past feeding experience can refine foraging and food choice. Insects can learn to associate sensory cues with components of food, such as sugars, amino acids, water, salt, alcohol, toxins and pathogens. In the fruit fly Drosophila some food components activate unique subsets of dopaminergic neurons that innervate distinct functional zones on the mushroom bodies. This architecture suggests that the overall dopaminergic neuron population could provide a potential cellular substrate through which the fly might learn to value a variety of food components. In addition, such an arrangement predicts that individual component memories reside in unique locations. Dopaminergic neurons are also critical for food memory consolidation and deprivation-state dependent motivational control of the expression of food-relevant memories. Here we review our current knowledge of how nutrient-specific memories are formed, consolidated and specifically retrieved in insects, with a particular emphasis on Drosophila.